2020
DOI: 10.1101/2020.07.13.20152694
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 misinformation: mere harmless delusions or much more? A knowledge and attitude cross-sectional study among the general public residing in Jordan

Abstract: Since the emergence of the recent coronavirus disease 2019 (COVID-19) and its spread as a pandemic, media was teeming with misinformation that led to psychologic, social and economic consequences among the global public. Probing knowledge and anxiety regarding this novel infectious disease is necessary to identify gaps and sources of misinformation which can help public health efforts to design and implement more focused interventional measures. The aim of this study was to evaluate the knowledge, attitude and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 60 publications
1
41
0
3
Order By: Relevance
“…Sallam et al observed that among students from Jordan, higher anxiety was associated with the belief that COVID-19 was the result of a global conspiracy [57]. The belief in conspiracy theories related to COVID-19 was also associated with a higher level of anxiety in the country's general population [101]. According to Liu and Tong, the exposure to updates or rumours about COVID-19 was associated with increased anxiety [102].…”
Section: Discussionmentioning
confidence: 99%
“…Sallam et al observed that among students from Jordan, higher anxiety was associated with the belief that COVID-19 was the result of a global conspiracy [57]. The belief in conspiracy theories related to COVID-19 was also associated with a higher level of anxiety in the country's general population [101]. According to Liu and Tong, the exposure to updates or rumours about COVID-19 was associated with increased anxiety [102].…”
Section: Discussionmentioning
confidence: 99%
“…[4,42] offered an examination of factors contributing to the acceptance of online health misinformation). Lower socioeconomic status, older age, and lower educational level groups are also disproportionally impacted by misinformation [48]. It is worthy to mention that among the results found by this line of research, studies also have shown contradictory results.…”
Section: Results Of Misinformation and Online Educationmentioning
confidence: 83%
“…It is worthy to mention that among the results found by this line of research, studies also have shown contradictory results. For example, some study argued that males tend to trust misinformation more than females [48], while other study contended that females accepted more health misinformation than their male counterparts [42].…”
Section: Results Of Misinformation and Online Educationmentioning
confidence: 99%
“…The field of misinformation is growing. Misinformation research has been growing rapidly on topics such as COVID 19 [2,4,48], vaccine [6; 9, 30, 49], climate change [13,16,36], medical concerns [56], communication [8], memory [22], cognitive impacts on reading [45], new literacies [11], online education [9], political studies [11,1], and diversity [42] etc.…”
Section: Review Of Related Literaturementioning
confidence: 99%